The Transparency of Government Financial Information Systems in Arab Countries: Evidence from Palestine - Khalil Abushamsieh; Antonio M. Lopez Hernandez; David Ortiz Rodriguez (Journal of Accounting, Business and Management (JABM), 2013)
Governments, researchers and international organizations are paying increasing attention to the issue of reforms in governmental financial reporting. Arab countries in general, and Palestine in particular, are working to develop their governmental financial information systems to make them more informative and transparent. This paper examines the extent to which Palestine has developed its governmental financial information system and analyses the most important factors underlying financial transparency. An analytical methodology is applied, using L ders Financial Management Reform Process Model (2001).